Carbon-Based Materials (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
New carbon materials with improved mechanical, electrical, chemical, and optical properties are predicted and considered to be very promising for practical application. Carbon-based materials in the form of films, fabrics, aerogels, or microstructural materials are known for their large surface areas and pore volumes, light weight, and a great variety of structural morphology. Such unique structures can then be employed for a variety of purposes, for example, the production of new electronic devices, energy storage, and the fabrication of new materials. Nowadays, clear understanding of carbon materials via several examples of synthesis/processing methodologies and properties characterization is required. This Special Issue, “Carbon-Based Materials”, addresses the current state regarding the production and investigation of carbon-based materials. It consists of 13 peer-reviewed papers that cover both theoretical and experimental works in a wide a range of subjects on carbon structures.